The Measure of Quality of the Environments' Turkish Validity and Reliability. (October 2019) - Akyurek, Gokcen; Bumin, Gonca
The aim of this study was to translate the Measure of Quality of the Environment–Short Form (MQE-SF) into Turkish language and to evaluate the validity and reliability. The MQE-SF was culturally adapted via an internationally suggested method. A total of 185 volunteers with disabilities (age range = 18-55 y/o, 107 males; 78 females) from the Disabled People Association of Turkey completed the MQE-SF. To evaluate the MQE-SF's criterion/concurrent validity, the Craig Hospital Inventory of Environmental Factors (CHIEF) was also administered. Test–retest reliability was evaluated by administering MQE-SF to 85 participants a second time within 14 days of initial administration. The alpha coefficient measuring the internal consistency of the questionnaire were .84 and .83. The criterion-related validity was moderate between the MQE-SF Barriers and the CHIEF ( r = –.46, p < .05). The questionnaire was moderately reliable in terms of the test–retest reliability ( r = .69, .70 p < .05). The Turkish adaptation of the MQE-SF had good internal consistency and moderate criterion-related validity as well as test–retest reliability for people with disabilities.